THE CONCEPT AND IMPORTANCE OF IDEAL CARDIOVASCULAR HEALTH - Jankovic, Janko (Medical Research, 2024)
Cardiovascular diseases (CVD) are the leading cause of death worldwide. In 2019, 17.9 million people died from CVD which accounts for 32% of all deaths globally. The burden of CVD in a given population is related to the cardiovascular health (CVH) of that population. The American Heart Association initiated in 2010 a new concept of ideal CVH focused on two groups, health behavior components (smoking, body mass index, physical activity, and diet) and health components (total cholesterol, blood glucose, and blood pressure). Ideal CVH is defined as the simultaneous presence of seven ideal CVH components or "Life’s Simple 7" (non-smoking, body mass index <25 kg/m2, level of physical activity up to the achievement of the set goal, diet in accordance with national recommendations, blood pressure <120/80 mm Hg, total cholesterol <200 mg/dL and blood glucose level <100 mg/dL) in the absence of clinically manifested CVD. The prevalence of ideal CVH is low worldwide and is less than 1% in the USA, China and Spain, and the lowest values ​​(0.02% and 0,1%) were recorded in the Republika Srpska, BH and Serbia, respectively. The ideal CVH is inversely related to the incidence and mortality rates of CVD, as well as overall mortality rates. People with the presence of a greater number of ideal CVH metrics (5, 6, and 7) are significantly less likely to suffer from CVD, ischemic heart disease and stroke and have lower mortality from CVD, as well as total mortality compared to people without one or only one ideal component of CVH. The status of CVH in the population is essential for predicting the risk of morbidity and mortality from CVD, which can be reduced by improving both health/biological and behavioral components of CVH.